Investigation of The Effects of Environmental Temperature Depending on Time on Geothermal Resource Parameters in Türkiye - Erdem, Murat; Gürtürk, Mert (My University, 2025)
Geothermal energy is a domestic energy source that is renewable, clean, and environmentally friendly. Türkiye is in a rich position among the world countries regarding geothermal energy due to its geological and geographical location. The vast majority of these resources are located in the western Anatolia region of the country. Today, geothermal energy obtained in the country is used in areas such as electricity generation, heating, thermal and health tourism, industrial mineral extraction, drying, etc. In this study, the potential of a geothermal energy source in Denizli was evaluated using the volumetric method. The effects of time-dependent both ambient temperature and resource were investigated on an hourly, monthly, and annual basis between 2001 and 2026. The analysis focused on the variation of resource temperature with ambient temperature and the efficiency of the Carnot cycle. The geothermal resource temperature was assumed to be 160°C, with a resource lifespan of 25 years. The lowest source temperature is 100.8°C, and the highest and lowest Carnot efficiencies are obtained as 40.4% and 16.5%. The geothermal resource potential has been calculated to be 74.97 MWe, and the thermal energy stored in the reservoir was determined to be 5.94×10¹5J.
Keywords: Renewable energy; Energy; Geothermal energy; Volumetric method